(3HZjI GdLdjS hGdeSGeQ hfRgI GdCQhM hGdNhGWQ aj GdCTYGQ hGdfhGOQs - (3TgGH GdOjf CMeO GdHTGQj GdMafGhjs
(3ChdgG (B:s
(3heG di Ef HPdJ HVGYJi s
(3BNQgG (B:s
(3hBNQ eG CYGf Gddg Ydi LeYg ai gPG GdcJGH GdeSei HZjI GdLdjS hbO aQZJ ef JCdjag G s
(3Hg CdaGX YGejI hCeKGd TYHjI cKjQIs
(3HgG fXGe GdJYbjHIs
(3JGQjN JCdjag ceG ai NGJeI GdeDda (B1183 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs